Pharmacological Modulation of the Short-Lasting Effects of Antagonistic Direct Current-Stimulation Over the Human Motor Cortex - Chaieb, Leila; Antal, Andrea; Terney, Daniella; Paulus, Walter (Frontiers in Psychiatry, 2012)
Combined administration of transcranial direct current stimulation (tDCS) with either pergolide (PGL) or D-cycloserine (D-CYC) can prolong the excitability-diminishing effects of cathodal, or the excitability enhancing effect of anodal stimulation for up to 24hrs poststimulation. However, it remains unclear whether the potentiation of the observed aftereffects is dominated by the polarity and duration of the stimulation, or the dual application of combined stimulation and drug administration. The present study looks at whether the aftereffects of oral administration of PGL (a D1/D2 agonist) or D-CYC (a partial NMDA receptor agonist), in conjunction with the short duration antagonistic application of tDCS (either 5 min cathodal followed immediately by 5 min anodal or vice versa), that alone only induces short lasting aftereffects, can modulate cortical excitability in healthy human subjects, as revealed by a single-pulse MEP (motor-evoked-potential) paradigm. Results indicate that the antagonistic application of DC currents induces short-term neuroplastic aftereffects that are dependent upon the polarity of the second application of short-duration tDCS. The application of D-cycloserine resulted in a reversal of this trend and so consequently a marked inhibition of cortical excitability with the cathodal-anodal stimulation order was observed. The administration of pergolide showed no significant aftereffects in either case. These results emphasise that the aftereffects of tDCS are dependent upon the stimulation orientation, and mirror the findings of other studies reporting the neuroplasticity inducing aftereffects of tDCS, and their prolongation when combined with the administration of CNS active drugs.